In search of paradise : the odyssey of an Italian family - Gabori, Susan, 1947- (McGill-Queen's studies in ethnic history, 1993)
Susan Gabori has woven the narrative of each character in the Pace family from interviews she conducted with Italian immigrants and their families to present an illuminating picture of people who, faced with a seemingly insensitive environment, must find a way to survive without sacrificing their dignity and pride. Each person finds a different way to hold on to some of the old while adapting to the new. With In Search of Paradise Gabori promotes a deeper understanding of and respect for the immigrant experience. The characters given a voice are Vincenzo, the father, Teresa, his wife, and their children, Franco, Roberto, Angelina, and Michele. Separated by Vincenzo's search for work in Libya and later by World War II, when the children are sent to a fascist school in Northern Italy and Vincenzo is sent to fight the British in Africa, they attempt to retain the bonds of family and culture. Reunited after the war, the economic climate in Italy forces Vincenzo and Franco to leave for Canada in 1950 in search of a better future. They are eventually joined by the rest of the family in Toronto.